If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -8) * 7 = a + -29 Reorder the terms: (-8 + a) * 7 = a + -29 Reorder the terms for easier multiplication: 7(-8 + a) = a + -29 (-8 * 7 + a * 7) = a + -29 (-56 + 7a) = a + -29 Reorder the terms: -56 + 7a = -29 + a Solving -56 + 7a = -29 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -56 + 7a + -1a = -29 + a + -1a Combine like terms: 7a + -1a = 6a -56 + 6a = -29 + a + -1a Combine like terms: a + -1a = 0 -56 + 6a = -29 + 0 -56 + 6a = -29 Add '56' to each side of the equation. -56 + 56 + 6a = -29 + 56 Combine like terms: -56 + 56 = 0 0 + 6a = -29 + 56 6a = -29 + 56 Combine like terms: -29 + 56 = 27 6a = 27 Divide each side by '6'. a = 4.5 Simplifying a = 4.5
| 6x+25=13x-52 | | 9x^3-1=0 | | (-3y+1)(-y-1)=0 | | 122-3X=33X+22 | | 10-9X=106-30X | | 3+3x=13+x | | 4x-4=12x-92 | | 6x+38=13x-39 | | 7-9x=26-16 | | 93-2x=4x+15 | | x-3=100 | | 8(x+2)-6x=21 | | 6X+57=10x+13 | | 8(x+2)-6=21 | | 0=3X+5 | | 3x^2=7 | | 4(x-1)=3x+6 | | 3(x-12)=x+8 | | 34x=-102 | | 4a+3=a+15 | | x+2=3z | | 32-4H+2H=22 | | 3x(9+10)= | | t^2=147 | | 6x=12-2x+4 | | x^4-2x-3=0 | | t^2=245 | | x^4=3 | | 0=2X+4 | | 13x-272=4x-11 | | 3x+19=11x-45 | | -6-3x=14-8x |